General phrase speaker verification using sub-word background models and likelihood-ratio scoring - Parthasarathy, Sarangarajan; Rosenberg, A. E. (In Proc. Int. Conf. on Spoken Language Processing, 1996)
The authors present a design and study the performance of a text-dependent speaker verification system using general phrase passwords. The text of the password utterance and its phone transcription are assumed to be available. The problems that are addressed include the appropriate choice of units for building target speaker models and the choice of background models for likelihood-ratio scoring.